RELEVANCE OF DEMOGRAPHIC CRITERION AT ESTABLISHING STATISTIC REGIONS IN CONTEXT PROBLEMS AND PROSPECTS OF EUROPEAN INTEGRATION - Jasmina Osmankovic; Emina Resic (European Regional Science Association (ERSA), 2010)
RELEVANCE OF DEMOGRAPHIC CRITERION AT ESTABLISHING STATISTIC REGIONS IN CONTEXT PROBLEMS AND PROSPECTS OF EUROPEAN INTEGRATION Within the process of defining statistic regionalization in the countries being candidates and the potential candidates, a demographic criterion is pointed out as the key one. It is a reason why we, in this work, concentrate on the criterion of demographic size while determining statistic (NUTS) regions in the European Union within the context of implementation of the Regulation on the establishing common classification of territorial units for the statistics. Regulation (EC) No 1059/2003 of the European Parliament and of the Council from May 26th, 2003 related to the establishment of common classification of territorial units for statistics. Within the work, we verify the hypothesis: that there is significant deviation from the criterion of demographic size at statistic (NUTS) regions in European Union. We verify the hypothesis by applying relevant statistic methods. Data basis for testing hypothesis is overtaken from the relevant tables of the Eurostat official website http://epp.eurostat.ec.europa.eu/portal/page/portal/statistics/search_database. Testing was performed in two steps. In the first step, 317 statistic regions of the second level (NUTS II) were analyzed. The second step analyzed 1,327 statistic regions of the third level (NUTS III). Both steps specifically analyzed deviation from minimal and maximal demographic size of statistic region belonging to corresponding level. The results are presented in tables and graphs. Actuality of research is determined by the Bosnia and Herzegovina obligation to define statistic regions (NUTS regions) so as by the fact that in the Bosnia and Herzegovina case non critical application of this criterion as the eliminatory one, may be in the conflict with the first criterion, or, existing administrative units and other criterions being relevant for the formation of regional structure.
Keywords: 330; demographic criterion; NUTS; statistic regions; integration